Effects of subcutaneous tirzepatide versus placebo or semaglutide on pancreatic islet function and insulin sensitivity in adults with type 2 diabetes: a multicentre, randomised, double-blind, parallel-arm, phase 1 clinical trial - Heise, Tim; Mari, Andrea; DeVries, J Hans; Urva, Shweta; Li, Jing; Pratt, Edward John; Coskun, Tamer; Thomas, Melissa K; Mather, Kieren J; Haupt, Axel; Milicevic, Zvonko (The lancet. Diabetes & endocrinology, 2022)
Tirzepatide, a dual glucose-dependent insulinotropic polypeptide (GIP)/GLP-1 receptor agonist, shows a remarkable ability to lower blood glucose, enabling many patients with long-standing type 2 diabetes to achieve normoglycaemia. We aimed to understand the physiological mechanisms underlying the action of tirzepatide in type 2 diabetes. This multicentre, randomised, double-blind, parallel-arm, phase 1 study was done at two centres in Germany. Eligible patients were aged 20–74 years, had type 2 diabetes for at least 6 months, and were being treated with lifestyle advice and stable doses of metformin, with or without one additional stable dose of another oral antihyperglycaemic medicine, 3 months before study entry. Via a randomisation table, patients were randomly assigned (3:3:2) to subcutaneously receive either tirzepatide 15 mg, semaglutide 1 mg, or placebo once per week. Endpoint measurements were done at baseline and the last week of therapy (week 28). The primary endpoint was the effect of tirzepatide versus placebo on the change in clamp disposition index (combining measures of insulin secretion and sensitivity) from baseline to week 28 of treatment and was analysed in the pharmacodynamic analysis set, which comprised all randomly assigned participants who received at least one dose of a study drug and had evaluable pharmacodynamic data. Safety was analysed in the safety population, which comprised all randomly assigned participants who received at least one dose of a study drug. Secondary endpoints included the effect of tirzepatide versus semaglutide on the change in clamp disposition index from baseline to week 28 of treatment, glucose control, total insulin secretion rate, M value (insulin sensitivity), and fasting and postprandial glucagon concentrations. Exploratory endpoints included the change in fasting and postprandial insulin concentrations. This study is registered with ClinicalTrials.gov, NCT03951753, and is complete. Between June 28, 2019, and April 8, 2021, we screened 184 individuals and enrolled 117 participants, all of whom were included in the safety population (45 in the tirzepatide 15 mg group, 44 in the semaglutide 1 mg group, and 28 in the placebo group). Because of discontinuations and exclusions due to missing or unevaluable data, 39 patients in each treatment group and 24 patients in the placebo group comprised the pharmacodynamic analysis set. With tirzepatide, the clamp disposition index increased from a least squares mean of 0·3 pmol m–2 L min–2 kg–1 (SE 0·03) at baseline by 1·9 pmol m–2 L min–2 kg–1 (0·16) to total 2·3 pmol m–2 L min–2 kg–1 (SE 0·16) at week 28 and, with placebo, the clamp disposition index did not change much from baseline (least squares mean at baseline 0·4 pmol m–2 L min–2 kg–1 [SE 0·04]; change from baseline 0·0 pmol m–2 L min–2 kg–1 [0·03]; least squares mean at week 28 0·3 [SE 0·03]; estimated treatment difference [ETD] tirzepatide vs placebo 1·92 [95% CI 1·59–2·24]; p<0·0001). The improvement with tirzepatide in clamp disposition index was significantly greater than with semaglutide (ETD 0·84 pmol m–2 L min–2 kg–1 [95% CI 0·46–1·21]). This result reflected significant improvements in total insulin secretion rate (ETD 102·09 pmol min–1 m–2 [51·84–152·33]) and insulin sensitivity (ETD 1·52 mg min–1 kg–1 [0·53–2·52]) for tirzepatide versus semaglutide. On meal tolerance testing, tirzepatide significantly reduced glucose excursions (lower insulin and glucagon concentrations) compared with placebo, with effects on these variables being greater than with semaglutide. The safety profiles of tirzepatide and semaglutide were similar, with gastrointestinal adverse events being the most common (11 [24%], 13 [30%], and seven [25%] with nausea; nine [20%], 13 [30%], and six [21%] with diarrhoea; and three [7%], five [11%], and one [4%] with vomiting, for tirzepatide, semaglutide, and placebo, respectively). There were no deaths. The glycaemic efficacy of GIP/GLP-1 receptor agonist tirzepatide in type 2 diabetes results from concurrent improvements in key components of diabetes pathophysiology, namely β-cell function, insulin sensitivity, and glucagon secretion. These effects were large and help to explain the remarkable glucose-lowering ability of tirzepatide seen in phase 3 studies. Eli Lilly.